The Perceived Enjoyment of the Online Courses in Digital Transformation Age: The Uses - Gratification Theory Approach - Khoa, Bui Thanh (2020 Sixth International Conference on e-Learning (econf), 2020)
Online learning is a useful method to help learners gain knowledge quickly and conveniently, regardless of space and time. As the Covid-19 pandemic is spreading and showing no signs of stopping, online learning has played an even more important role, especially when governments' social isolation order is fully applied. Massive Open Online Courses (MOOCs), which are more and more popular worldwide, bring many benefits to the learner for improving skills and knowledge. The Uses & Gratification Theory (U&G theory) is one theory that can discover the relationship between user-centric motivation and user attitude when they use the media. Based on the Uses & Gratification theory, this study aimed to analyze the relationship between the learner's motivation and attitude when taking part in an online course. The quantitative research model was applied through a survey of 316 respondents. The result pointed out that motivational factors affect Perceived Enjoyment in online courses on the website, including Convenience, Entertainment, Socialising, and Experience Sharing. Some managerial implications were proposed.